University English for Academic Purposes in China A Phenomenological Interview Study - Rao, Xiaofei (Springer Singapore, 2018)
This book uses an in-depth, phenomenological interview approach to explain the generational characteristics of today's Chinese university youths and the critical dispositions they believe indispensable in acquiring English as an academic language in and outside school settings. By presenting the authentic voices of the recruited participants, the book clarifies how English for academic purposes (EAP), as an emerging global phenomenon and a research-informed practice, enables and empowers them for conscious self-transformation and critical awareness development through language study. The book also explores issues arising in the fields of general English language teaching as well as traditional and critical EAP, and discusses university English language learners' learning needs and rights. The book further promotes a dynamic and transformative University EAP pedagogy of particularity, practicality, and possibility moving from the oppression of language education to its liberation, and the increasing critical consciousness among the present and future university youths in a time of great social changes.